Here is my own implementation of nub (remove duplicates):
nub :: (Eq a) => [a] -> [a]
nub lista = nub_rec lista []
where
nub_rec :: (Eq a) => [a] -> [a] -> [a]
nub_rec [] acc = acc
nub_rec (x:xs) acc = nub_rec (filter (\y -> if y == x then False else True) xs) (x:acc)
I consider how to use foldr/foldl to implement nub, could you help me ? I can't see a way.
First, your implementation of nub is bit more complex than it needs to be (and it reverses the order of elements in the list). Here's a simpler one:
myNub :: Eq a => [a] -> [a]
myNub (x:xs) = x : filter (/= x) (myNub xs)
myNub [] = []
Now, if we want to use foldr to write a function that will output, not just an "aggregate" but a full list, it's useful to first have a look at the simplest foldr-based function that takes in a list and spits out a list:
myNoop :: [a] -> [a]
myNoop l = foldr (\ x xs -> x : xs) [] l
Given that, the filter must be inserted somewhere. Since I assume this is a homework, I'll leave that to the OP as an exercise :)
Solution only with filter and foldr without direct (or self) recursion:
removeDuplicates :: Eq a => [a] -> [a]
removeDuplicates = foldr (\z ys -> z : filter (/= z) ys) []
Related
I'm trying to reverse list of lists in Haskell by using foldr. There is an example of what I want to do:
> reverse'' [[1,2,3],[3,4,5]]
[[5,4,3],[3,2,1]]
And my code (it is not working):
reverse'':: [[a]]->[[a]]
reverse'' x = foldr (\n acum -> acum:(foldr(\m acum1 -> acum1++[m])) [] n) [[]] x
My IDE reports me an error at the start of the second foldr.
To analyse your current solution, I've broken down your one-liner into some helper functions, with their type deduced based on their composition:
reverse'':: [[a]] -> [[a]]
reverse'' x = foldr f [[]] x
where
f :: [a] -> a -> [a]
f n acum = acum : reverse n
reverse :: [a] -> [a]
reverse n = foldr append [] n
append :: a -> [a] -> [a]
append m acum = acum ++ [m]
When I try to compile the above, ghc complains with the following error for the type signature of reverse'':
Expected type: [[a]] -> [[a]] -> [[a]]
Actual type: [[a]] -> [a] -> [[a]]
I did some digging, and in order for reverse'' to have the type [[a]] -> [[a]], the function f needs to have the type [a] -> [[a]] -> [[a]]. However the current f has type [a] -> a -> [a], or in this case [[a]] -> [a] -> [[a]].
The following has the correct type, but inserts an extra [] value into the start of the array, due to the starting value of the accumulator:
reverse'':: [[a]] -> [[a]]
reverse'' x = foldr f [[]] x
where
f :: [a] -> [[a]] -> [[a]]
f n acum = acum ++ [reverse n]
reverse :: [a] -> [a]
reverse n = foldr append [] n
append :: a -> [a] -> [a]
append m acum = acum ++ [m]
The final solution
By changing the initial accumulator value to the empty list [], as opposed to a list of an empty list [[]], we end up at a working solution:
reverse'':: [[a]] -> [[a]]
reverse'' x = foldr f [] x
where
f :: a -> [a] -> [a]
f n acum = acum ++ [reverse n]
reverse :: [a] -> [a]
reverse n = foldr append [] n
append :: a -> [a] -> [a]
append m acum = acum ++ [m]
As a single line
If you really want this as a one-liner, here it is:
reverse'' :: [[a]] -> [[a]]
reverse'' = foldr (\n acum -> acum ++ [foldr (\m acum1 -> acum1 ++ [m]) [] n]) []
With working:
append m acum = acum ++ [m]
append = \m acum1 -> acum1 ++ [m]
reverse n = foldr append [] n
reverse = \n -> foldr append [] n
reverse = foldr append []
reverse = foldr (\m acum1 -> acum1 ++ [m]) []
f n acum = acum ++ [reverse n]
f = \n acum -> acum ++ [reverse n]
f = \n acum -> acum ++ [foldr (\m acum1 -> acum1 ++ [m]) [] n]
reverse'':: [[a]] -> [[a]]
reverse'' x = foldr f [] x
reverse'' x = foldr (\n acum -> acum ++ [foldr (\m acum1 -> acum1 ++ [m]) [] n]) [] x
reverse'' = foldr (\n acum -> acum ++ [foldr (\m acum1 -> acum1 ++ [m]) [] n]) []
Appendix: An explicitly recursive solution
Here is an explicitly recursive solution (i.e. not using a fold), with definitons of map and reverse provided.
reverse :: [a] -> [a]
reverse (x:xs) = reverse xs ++ [x]
reverse [] = []
map :: (a -> b) -> [a] -> [b]
map f (x:xs) = f x : map f xs
map _ [] = []
reverse'' :: [[a]] -> [[a]]
reverse'' ls = reverse $ map reverse ls
I am learning Haskell at the moment and have come to a bit of a standstill. I'm trying to write a function that takes a predicate p and a list xs and returns the list of those elements of xs which immediately follow an element which passes the predicate p. Here is what I have :
afterFilter :: (a -> Bool) -> [a] -> [a]
afterFilter x (y:ys) =
if x y
then (map head [ys])
else
afterFilter x (tail ys)
test input : afterFilter (<0) [-4,7,-4,-8,3,-3,-6,0,-9,-1]
output : [7]
The trick is to pull two elements out of the input list by pattern-matching two cons cells. If the first element passes the predicate, we stick the second on the output. But don't forget to stick the second element back on the input list when you make the recursive call.
afterFilter :: (a -> Bool) -> [a] -> [a]
afterFilter f [] = [] -- input list is empty
afterFilter f [x] = [] -- input list has only one element - no "next element" to return
afterFilter f (x:y:xs) =
let ys = afterFilter f (y:xs)
in (if f x then y:ys else rest)
However, a higher-level - and much more Haskellish - way to approach the problem would be to break it down into a pipeline of operations.
Pair up each item in the list with the element that follows it using zip, so we have a list of (element, next) pairs.
Use filter to drop the pairs for which element does not pass the predicate.
Use map to extract the next part of each surviving pair.
So the code looks like this:
pairWithSuccessors :: [a] -> [(a, a)]
pairWithSuccessors xs = zip xs (tail xs)
afterFilter :: (a -> Bool) -> [a] -> [a]
afterFilter p xs =
let withSuccessors = pairWithSuccessors xs (tail xs)
filtered = filter (\(element, next) -> p element) withSuccessors
filteredSuccessors = map (\(element, next) -> next) filtered
in filteredSuccessors
Or, written in point-free style:
afterFilter p = map snd . filter (p . fst) . pairWithSuccessors
Functions built with the composition operator . are read right-to-left: first pairWithSuccessors, then filter (p . fst), then map snd over the result.
GHC is good at working with lists: when compiled with optimisations, both approaches should produce roughly the same machine code - that is, there's no performance cost to the high-level solution
Following what you did, there are some strange things with your code :
The map head [ys] is very odd, and causes your function to stop : At the first element matching the predicate, your function returns a list containing its immediate successor and stops there. You still need to process the rest of the list.
Also, following your definition of the problem, each item which is a successor of an item passing the predicate should be on the resulting array. I may be wrong, but what I understood is that afterFilter (<0) [-1, -1, 1] should return [-1, 1].
However, you're discarding one element you didn't check for by calling tail ys : You checked for y, but not for head ys.
Finally, by adding the edge cases, here is what you get :
afterFilter :: (a -> Bool) -> [a] -> [a]
afterFilter _ [] = []
afterFilter _ [_] = []
afterFilter x (y:ys#(z:zs)) =
if x y
then z : afterFilter x ys
else
afterFilter x ys
Try:
afterFilter :: (a -> Bool) -> [a] -> [a]
afterFilter p [] = []
afterFilter p [_] = []
afterFilter p (x1:x2:xs)
| p x1 = x2:rest
| otherwise = rest
where rest = afterFilter p (x2:xs)
Or
afterFilter' :: (a -> Bool) -> [a] -> [a]
afterFilter' p xs = map snd $ filter (\(x, _) -> p x) $ zip xs (tail xs)
Or
afterFilter'' :: (a -> Bool) -> [a] -> [a]
afterFilter'' p xs = [y | (x, y) <- zip xs (tail xs), p x]
merge :: [a] -> [a] -> [a]
merge xs [] = xs
merge [] ys = ys
merge (x:xs) (y:ys) = x : y : merge xs ys
maxOfTwoLists [x] [y] = maximum (merge [x] [y])
I am trying to combine the two lists then find the max value in the single list. It compiles but when i call maxOfTwoLists it gives me a non-exhaustive patterns error. My merge returns a single list just fine, and maximum takes a single list. So it feels like it should be working.
If you're looking to merge two lists, the builtin concat would help. It flattens a list, so we could do the following:
maxOfTwoLists :: (Ord a) => [a] -> [a] -> a
maxOfTwoLists xs ys = maximum $ concat [xs,ys]
In which, $ means to evaluate the result of the right side function before applying it to the left side function.
As #badcook notes the pattern match isn't quite right.
merge :: [a] -> [a] -> [a]
merge xs [] = xs
merge [] ys = ys
merge (x:xs) (y:ys) = x : y : merge xs ys
maxOfTwoLists :: (Ord a) => [a] -> [a] -> a
maxOfTwoLists [] ys = maximum ys
maxOfTwoLists xs [] = maximum xs
maxOfTwoLists xs ys = maximum (merge xs ys)
I'll guess you wrote the merge function as an exercise but you can also use ++ from Prelude to append one list to another.
maxOfTwoLists :: (Ord a) => [a] -> [a] -> a
maxOfTwoLists xs ys = maximum (xs ++ ys)
Output:
λ> maxOfTwoLists [1,2,3] [4,5,6]
6
λ> maxOfTwoLists [1,2,3] []
3
λ> maxOfTwoLists [] [1,2,3]
3
λ>
I am trying to enumerate all the possible merges of two lists.
In example inserting "bb" into "aaa" would look like
["bbaaa", "babaa", "baaba", "baaab", "abbaa", "ababa", "abaab", "aabba", "aabab", "aaabb"]
What I currently did is this
import Data.List
insert'' :: Char -> String -> [(String, String)] -> String
insert'' _ _ ([]) = []
insert'' h b ((x, y):xs) =
(x ++ [h] ++ (insert' (b, y))) ++ (insert'' h b xs)
insert' :: (String, String) -> String
insert' ([], ys) = ys
insert' (xs, ys) =
insert'' h b lists
where
h = head xs
b = tail xs
lists = zip (tails ys) (inits ys)
This returns for ("aaa", "bb")
"bbaaababaaabaababbaababaababbabababb"
a concatenated string, I tried making it a list of strings, but I just cannot wrap my head around this function. I always seems to get infinite type construction.
How could I rewrite the function, so it would return a list of strings?
An other implementation idea as in Daniel Wagners first post is to choose in each step a element from one of the lists and prepending it to the results generated by the function called with only the remaining parts of the list:
interleave :: [a] -> [a] -> [[a]]
interleave xs [] = [xs]
interleave [] ys = [ys]
interleave xs#(x : xs') ys#(y : ys') =
map (x :) (interleave xs' ys) ++ map (y :) (interleave xs ys')
For your intial example this produces:
ghci> interleave "bb" "aaa"
["bbaaa","babaa","baaba","baaab","abbaa","ababa","abaab","aabba","aabab","aaabb"]
Here is one implementation idea: for each element in the first list, we will choose (nondeterministically) a position in the second list to insert it, then recurse. For this to work, we first need a way to nondeterministically choose a position; thus:
choose :: [a] -> [([a], [a])]
choose = go [] where
go before xs = (before, xs) : case xs of
[] -> []
x:xs -> go (x:before) xs
For example:
> choose "abcd"
[("","abcd"),("a","bcd"),("ba","cd"),("cba","d"),("dcba","")]
Now we can use this tool to do the insertion:
insert :: [a] -> [a] -> [[a]]
insert [] ys = [ys]
insert (x:xs) ys = do
(before, after) <- choose ys
rest <- insert xs (reverse after)
return (before ++ [x] ++ rest)
In ghci:
> insert "ab" "cde"
["abcde","aebcd","adebc","acdeb","cabde","caebd","cadeb","dcabe","dcaeb","edcab"]
In this answer, I will give the minimal change needed to fix the code you already have (without completely rewriting your code). The first change needed is to update your type signatures to return lists of strings:
insert'' :: Char -> String -> [(String, String)] -> [String]
insert' :: (String, String) -> [String]
Now your compiler will complain that the first clause of insert' is returning a String instead of a [String], which is easily fixed:
insert' ([], ys) = [ys]
...and that the second clause of insert'' is trying to append a String to a [String] when running [h] ++ insert' (b, y). This one takes some thinking to figure out what you really meant; but my conclusion is that instead of x ++ [h] ++ insert' (b, y), you really want to run \t -> x ++ [h] ++ t for each element in insert' (b, y). Thus:
insert'' h b ((x, y):xs) =
(map (\t -> x ++ [h] ++ t) (insert' (b, y))) ++ (insert'' h b xs)
The complete final code is:
import Data.List
insert'' :: Char -> String -> [(String, String)] -> [String]
insert'' _ _ ([]) = []
insert'' h b ((x, y):xs) =
(map (\t -> x ++ [h] ++ t) (insert' (b, y))) ++ (insert'' h b xs)
insert' :: (String, String) -> [String]
insert' ([], ys) = [ys]
insert' (xs, ys) =
insert'' h b lists
where
h = head xs
b = tail xs
lists = zip (tails ys) (inits ys)
Now ghci will happily produce good answers:
> insert' ("aaa", "bb")
["bbaaa","babaa","baaba","baaab","abbaa","ababa","abaab","aabba","aabab","aaabb"]
I'm trying to write a function named split that takes a list and returns a list of pairs of all the different possiblities to partition it, e.g.
split [4,3,6] = [([],[4,3,6]),([4],[3,6]),([4,3],[6]),([4,3,6],[])]
Now I wrote this
split :: [a] -> [([a],[a])]
split [] = [([],[])]
split (x:xs) = ([],(x:xs)):(zip (map (x:) (map fst split(xs))) (map snd split(xs)))
piece of code and Hugs and the interpreter of my choice gets me this
ERROR file:.\split.hs:3 - Type error in application
*** Expression : map snd split xs
*** Term : map
*** Type : (e -> f) -> [e] -> [f]
*** Does not match : a -> b -> c -> d
error message. What the heck am I doing wrong? Why would (map snd split xs) be of type
(a-> b -> c -> d)?
You've misplaced your parens. Try
split (x:xs) = ([],(x:xs)):(zip (map (x:) (map fst (split xs))) (map snd (split xs)))
Haskell doesn't use parenthesis for function calls in the same way as something like C and Java. When you write map fst split(xs) this is the same as map fst split xs, i.e. the compiler thinks that you are trying to call map with three parameters. Therefore you need to parenthise the call to split like this: map fst (split xs).
What you are effectively trying to write is a simple zipper for a list. The easiest way to implement it is
import Data.List (inits, tails)
split xs = zip (inits xs) (tails xs)
Here's an alternative definition:
splits :: [a] -> [(a, a)]
splits xs = map (flip splitAt xs) [0 .. length xs]
Admittedly, it's not very efficient, but at least it's concise :-)
Another version that's even shorter, and probably more efficient, using inits and tails from Data.List:
splits :: [a] -> [(a, a)]
splits xs = zip (inits xs) (tails xs)
Now let's have a little fun. We can write inits and tails as foldrs, where we use initsA and tailsA to represent what are known as the algebras of the folds:
inits :: [a] -> [[a]]
inits = foldr initsA [[]]
initsA :: a -> [[a]] -> [[a]]
initsA x xss = [] : map (x:) xss
tails :: [a] -> [[a]]
tails = foldr tailsA [[]]
tailsA :: a -> [[a]] -> [[a]]
tailsA x xss = (x : head xss) : xss
Using these algebras, we can further combine them:
splits :: [a] -> [([a], [a])]
splits = foldr splitsA [([], [])]
splitsA :: a -> [([a], [a])] -> [([a], [a])]
splitsA xy xyss = zip (initsA xy xss) (tailsA xy yss)
where (xss, yss) = unzip xyss
So now we have splits defined as a single foldr!